Water conservation and wastewater treatment in BRICS nations : technologies, challenges, strategies and policies - Singh, Pardeep (Elsevier, 2020)
Water Conservation and Wastewater Treatment in BRICS Nations: Technologies, Challenges, Strategies, and Policies addresses issues of water resources--including combined sewer system overflows--assessing effects on water quality standards and protecting surface and sub-surface potable water from the intrusion of saline water due to sea level rise. The book's chapters incorporate both policies and practical aspects and serve as baseline information for future adaption plans in BRICS nations. Users will find detailed important information that is ideal for policymakers, water management specialists, BRICS nation undergraduate or university students, teachers and researchers. --